The relationship between corporate image, customer satisfaction and customer loyalty : the case study of coca-cola company in the Gambia - Jallow, Hawa
The Coca-Cola Company in the Gambia faces various challenges especially in relation to customer loyalty. Many customers boycott the company's products due to religious sensitivity. This problem affects the company's productivity, which might be due to ineffective marketing strategies. The ability to link customer satisfaction with customer loyalty is important in determining the effect of customer satisfaction on organisational performance. Hence, this study aims to determine the influence of corporate image on customer loyalty towards The Coca-Cola Company in the Gambia, particularly how customer satisfaction mediates the relationship between corporate image and customer loyalty. Data were collected from customers of The Coca-Cola Company in the Gambia using cluster sampling and simple random sampling. Structured questionnaires with 10- point Likert scale were administered to the respondents selected through the above sampling procedure. The data were analysed using Structural Equation Modelling (SEM) via IBM SPSS 25.0 and IBM SPSS AMOS 25.0. The findings showed that corporate image has significant effects on customer satisfaction, while customer satisfaction has significant effect on customer loyalty. However, corporate image has no significant effect on customer satisfaction. The findings showed that mediation effects exist since the indirect effects are significant. It is full mediation since the direct effect is not significant. This indicates that customer satisfaction is an important variable that connects the corporate image with customer loyalty, specifically for Coca-Cola products in the Gambia. This study has made significant theoretical, practical and methodological contributions to this research area by developing the first model of the influence of corporate image on customer loyalty for Coca-Cola products in the Gambia. The model entails construct of corporate image, customer loyalty and customer satisfaction. This model could help the management and decision makers in developing and implementing marketing related policies.